The Americleft Project: A Proposed Expanded Nasolabial Appearance Yardstick for 5- to 7-Year-Old Patients with Complete Unilateral Cleft Lip and Palate (CUCLP). (January 2016) - Mercado, A.M.; Russell, K.A.; Daskalogiannakis, J.; Hathaway, R.R.; Semb, G.; Ozawa, T.; Smith, A.; Lin, A.Y.; Long, R.E.
Objective: To develop a yardstick of reference photographs for nasolabial appearance assessments of 5- to 7-year-old patients with complete unilateral cleft lip and palate (CUCLP). Design: Blind retrospective analysis of clinical records and comparison to historical controls. Patients: Subjects were two groups of 6- to 12-year-olds (n = 124 and n = 135) and one group of 5- to 7-year-olds (n = 149) with nonsyndromic CUCLP from three previous Americleft studies, including cohorts from seven different cleft/craniofacial centers. Interventions: All patients received the infant management protocols of their respective centers. Eleven trained and calibrated judges (five participated in all three studies) did blind ratings of nasolabial appearance using the Asher-McDade method. Main Outcome Measures: Patients receiving the most consistent ratings between judges, selected first from the groups of 6- to 12-year-olds, were used to create a pilot yardstick for eventual use in the third study of 5- to 7-year-olds. For each of the Asher-McDade categories, 8 of the 5- to 7-year-old patients receiving the most consistent scores between raters were ranked by 10 judges for a final elimination to leave three per category. Results: Using this method of successive changes in rating methods, a new reference yardstick for nasolabial appearance rating was established and linked to the original Asher-McDade method as well as the single examples in a previously published yardstick for patients with CUCLP. Pilot testing using the yardstick improved reliabilities. Conclusions: Use of an expanded nasolabial yardstick of reference photographs representative of the range of possibilities of each of the five Asher-McDade categories is now available to see if reliability of these ratings can be improved.